Relative age effect? No "flipping" way: exploring the relative age effect in elite, female gymnastics - Langham-Walsh, E.; Gottwald, V.; Hardy, J. (2019 SCAPPS Conference. Vancouver, BC, Canada, October 17 -19, 2019, 2019)
The relative age effect (RAE) is a biased distribution of athlete birthdates, with an over-representation and greater success rate of those born earlier in the year. Converse to team-sport contexts, where early maturation is often associated with superior physical attributes, delayed maturation has been observed in higher skilled performers within gymnastics. In this instance, we might expect a more atypical RAE and perhaps, bias towards relatively younger athletes within the system. The present research examined the presence of a RAE within a sample of elite, female gymnasts. We acquired archival data from 2015 until present. Date of births of elite, female gymnasts who had competed internationally since 2015 (N = 806, Mage = 20.63, Ncountries = 89), were obtained from an online database using the rvest package in R Studio. Birth quartiles were assigned based on the calendar year consistent with the selection year adopted in gymnastics. Chi squared analysis indicated no presence of a RAE, ?2 (3, 806) = 2.91,p = 0.41). There are several underlying mechanisms that may account for this null finding. Firstly, gymnastics often acts as a potential donor sport for alternative sports (see Athletic Skills Model). Furthermore, Q1 athletes, who may be succeeding in other sports where RAEs are more pronounced, may move from gymnastics into another sport. A "wash out" effect may also provide explanation for the lack of RAE as the sample contained gymnasts at varying levels of international representation as well as those favoured by different task demands across apparatuses.